PENGARUH PENGEMBANGAN KARIR DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA PERAWAT (Studi Pada RSJD Dr. Amino Gondohutomo Provinsi Jawa Tengah) - Fitriani, Fitriani; Mohklas, Mohklas (JAB (Jurnal Akuntansi & Bisnis), 2015)
This study aims to determine the effect of career development and organizational commitment partially and simultaneously to job satisfaction of nurses in RSJD Dr. Amino Gondohutomo Central Java Province. The variable in this study is divided into two, independent and dependent variables. The independent variables consist of career development and organizational commitment and the dependent variable is job satisfaction of nurses. The population in this study is nurses in RSJD Dr. Amino Gondohutomo Central Java province and the sample is a nurse with a total of 80 people. This research was conducted by testing the validity and reliability of the instrument, then the data were analyzed using multiple linear regression analysis and hypothesis testing, including: t test, F test and the coefficient of determination. The analysis showed the career development have a positive effect on job satisfaction of nurses partially and organizational commitment has positive influence on job satisfaction of nurses partially. While simultaneously career development and organizational commitment has positive influence on job satisfaction of nurses. Keywords: Career Development, Organizational Commitment, and Job Satisfaction.